2023
DOI: 10.1021/acsami.3c05540
|View full text |Cite
|
Sign up to set email alerts
|

Flexible Self-Powered Friction Piezoelectric Sensor Based on Structured PVDF-Based Composite Nanofiber Membranes

Abstract: With the rapid development of the economy and technology, intelligent wearable devices have gradually entered public life. Flexible sensors, as the main component of wearable devices, have been widely concerned. However, traditional flexible sensors need an external power supply, lacking flexibility and sustainable power supply. In this study, structured poly­(vinylidene fluoride) (PVDF)-based composite nanofiber membranes doped with different mass fractions of MXene and zinc oxide (ZnO) were prepared by elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…The calculation show that the β-phase fraction of pure PVDF-HFP is about 66.3 %, while the β-phase fraction of ZnO- PVDF-HFP increased to 76.8 %, which will lead to better piezoelectric properties. Many researchers have reported that the surface charges on the ZnO nanofillers interact with the molecular dipoles (CH 2 or CF 2 ) of PVDF-HFP and improves the β-phase content of the composites [ 30 , 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…The calculation show that the β-phase fraction of pure PVDF-HFP is about 66.3 %, while the β-phase fraction of ZnO- PVDF-HFP increased to 76.8 %, which will lead to better piezoelectric properties. Many researchers have reported that the surface charges on the ZnO nanofillers interact with the molecular dipoles (CH 2 or CF 2 ) of PVDF-HFP and improves the β-phase content of the composites [ 30 , 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…Our research group proposed a new strategy to prepare a high-performance capacitive flexible pressure sensor based on MXene/Polyvinylpyrrolidone (PVP) through interdigital electrodes. [43] By increasing the number of interdigital [51] Copyright 2023, American Chemical Society. b) Reproduced with permission.…”
Section: Other Mechanisms and Effectsmentioning
confidence: 99%
“…Common piezoelectric materials include Polyvinylidene fluoride trifluoroethylene (P (VDF-TrFE)), Barium titanate (BaTiO 3 ), Lead zirconate titanate (PZT), zinc oxide (ZnO), etc. [51][52][53][54][55][56][57][58][59][60] The following will be introduced separately.…”
Section: Piezoelectric Type Sensormentioning
confidence: 99%
See 2 more Smart Citations